A pilot study of the effect of rivaroxaban in sickle cell anemia. Issue 6 (4th March 2021) - Ataga, Kenneth I.; Elsherif, Laila; Wichlan, David; Wogu, Adane F.; Matsui, Neil; Pawlinski, Rafal; Cai, Jianwen; Key, Nigel S.
Abstract: Introduction: The contribution of coagulation activation to the pathogenesis of sickle cell disease (SCD) remains incompletely defined. We evaluated the efficacy and safety of rivaroxaban, an oral direct factor Xa inhibitor, in subjects with sickle cell anemia. Materials and Methods: In this pilot, single‐center, randomized, double‐blind, placebo‐controlled, crossover study, eligible subjects with sickle cell anemia received rivaroxaban or placebo. The effect of rivaroxaban on coagulation activation, endothelial activation, inflammation, and microvascular blood flow was evaluated. Results: Fourteen patients (HbSS – 14; females – 9) with mean age of 38 ± 10.6 years were randomized to receive rivaroxaban 20 mg daily or placebo for 4 weeks and, following a 2‐week washout phase, were "crossed‐over" to the treatment arm opposite to which they were initially assigned. Mean adherence to treatment with rivaroxaban, assessed by pill counts, was 85.6% in the first treatment period and 93.6% in the second period. Treatment with rivaroxaban resulted in a decrease from baseline of thrombin‐antithrombin complex versus placebo (−34.4 ug/L [95% CI: −69.4, 0.53] vs. 0.35 ug/L [95% CI: −3.8, 4.5], p  = .08), but the difference was not statistically significant. No significant differences were observed in changes from baseline of D‐dimer, inflammatory, and endothelial activation markers or measures of microvascular blood flow. Rivaroxaban was well tolerated. Conclusions: Rivaroxaban was safe but did not significantly decrease coagulation activation, endothelial activation, or inflammation. Rivaroxaban did not improve microvascular blood flow. Adequately powered studies are required to further evaluate the efficacy of rivaroxaban in SCD. Clinicaltrials.gov Identifier: NCT02072668.